Hubungan Konsumsi Seafood dengan Riwayat Hiperkolesterol pada Pria Usia Pra Lansia di Desa Laronanga Kabupaten Konawe Utara Provinsi Sulawesi Tenggara - Prasetya, Fikki (Sekolah Tinggi Ilmu Kesehatan Karya Kesehatan, 2016)
Seafood is an excellent source of protein, fat, vitamins, and minerals (zinc, iron, selenium, magnesium, and iodine). But if seafood consumption becomes a habit and excessive will be not good for health because seafood contains high purines and fats and can increase cholesterol levels (Prayitno, 2014). This study aims to determine the relationship between seafood consumption and history of hypercholesterolemia in pre-elderly and elderly men. This research is an analytical descriptive with a correlational design and a cross sectional approach. The population in this study were all the people of Laronanga Village who came for treatment at the Andowia Health Center who carried out laboratory examinations related to the examination of total cholesterol levels and had a history of hypercholesterolemia, male sex with pre-elderly age, as many as 40 people and a sample of 36 people who taken using purposive sampling, data obtained using a questionnaire and tested using the Chi Square test. The results showed that of the 36 respondents studied, respondents who were at risk of consuming seafood and did not have a history of hypercholesterolemia were 0 respondents (0%) and who had a history of hypercholesterolemia were 33 respondents (91.7%), while not at risk of consuming seafood and not having high cholesterol. history of hypercholesterolemia amounted to 2 respondents (5.6%) and those who were not at risk and had a history of hypercholesterolemia amounted to 1 respondent (33.3%). There is a relationship between the habit of consuming seafood with a history of hypercholesterolemia in pre-elderly men, with p value = 0.005 < a = 0.05